Analysis of Determinants of Demand and Supply of Maize in Aniocha North Local Government Area, Delta State, Nigeria - A.I.N, Kaine; Iku, J.E; Ebigwai, S.J (International Journal of Sustainable Agricultural Research, 2015)
This study on the analysis of determinants of demand and supply of maize was conducted in Aniocha North Local Government Area, Delta State with particular emphasis on some selected villages in the Local Government. The study covered forty maize producers randomly selected from eight villages from randomly selected two clans in the study area. Frequencies, means percentages and chi-square statistics were employed in the determining the data obtained. Chi-square statistics was used to ascertain whether socio-economic factors are significant determinants of demand and supply of maize in the study area. The result shows that the value of C hi-square calculated (2.45) < chi-square critical value (14.1) at five percent level of significance with degree of freedom of seven as was conducted. This implies that socio-economic characteristics were not significant determinants of demand and supply of maize. The result agrees with the null hypothesis which says that socio-economic characteristics are not significant determinants of demand and supply of maize in the study area. Hence it was accepted.